RETRACTION NOTE TO "DEVELOPMENT OF METHOD TO ASSESS SEPARATION PROCESS TAKING INTO ACCOUNT RHEOLOGICAL PROPERTIES OF MINERAL SLURRY" - Aleksandrova, Tatiana; Potemkin, Vasim (Journal of Applied Engineering Science, 2022)
This article has been retracted at the request of the Editor-in-Chief, in line with journal Publication Ethics based on guidelines and standards developed by the Committee on Publication Ethics (COPE). This article has been retracted at the request of the authors, because they determined mistakes in conducted research which demand additional check and clarification. Therefore, the results and conclusions could be incorrect. Both autors, Vadim Potemkin and Tatiana Aleksandrova, agree to this retraction.The Authors and Editors would like to apologize to readers for not uncovering these issues duringthe editorial process.Retracted paper detailsAuthors: Vadim Potemkin*, Tatiana Aleksandrova (*corresponding author)Affiliation: Saint Petersburg Mining University, Mineral Processing Department, Saint Petersburg, Russian FederationDOI: 10.5937/jaes0-31764JAES Paper identification: 19(2021)4, 894, 1120-1125